2010
DOI: 10.1177/1056492609357009
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Decision Vortex: Lessons From the Emergency Room

Abstract: The dominant model of decision making, rational decision making, is increasingly challenged by research on intuitive decision making and emotion. This article contributes to the debate by articulating a model of how rational decision making, intuitive decision making, and emotion influence each other: the critical decision vortex. The critical decision vortex emerges from a discussion between an emergency room (ER) doctor and a management scholar. The experience of the doctor diagnosing and treating patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 55 publications
1
20
0
1
Order By: Relevance
“…For example, decisions to stand or sit and whether or not to intervene influenced interactions between facilitators and, relatedly, their affective experience. Supporting this observation is research by Coget and colleagues (Coget and Keller 2010), who found that effects of the same discrete emotion on the choice of intuitive vs. rational information processing differed according to the previous emotional experiences of the decision maker.…”
Section: Theory Contributionssupporting
confidence: 59%
See 1 more Smart Citation
“…For example, decisions to stand or sit and whether or not to intervene influenced interactions between facilitators and, relatedly, their affective experience. Supporting this observation is research by Coget and colleagues (Coget and Keller 2010), who found that effects of the same discrete emotion on the choice of intuitive vs. rational information processing differed according to the previous emotional experiences of the decision maker.…”
Section: Theory Contributionssupporting
confidence: 59%
“…This state is in a constant flux. As with the interactions of medical practitioners in the critical decisions vortex (Coget and Keller 2010) where analytical and intuitive processing fluidly interact; this small workshop shows a more nuanced and dynamic flux occurs within, between and among individuals, and appears to be more immediate. So, whilst decision-making is a single time point, it is possible that a different multiplicity of states at different time points would result in materially different decisions at another single time-point.…”
Section: Theory Contributionsmentioning
confidence: 99%
“…Many authors endorsed EI as an important component of leadership development for physicians in general, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] for successfully navigating the business of medicine for physician executives, [38][39][40][41][42][43][44][45][46][47][48] in academic settings, [49][50][51] for developing effective social networks in health care, 52 as a leadership component across specialties, [53][54][55][56][57][58][59][60][61][62][63][64][65] and as a way of partnering with patients. 66,67 Two studies (1 a...…”
Section: Ei Is a Key Component Of Medical Leader Developmentmentioning
confidence: 99%
“…Nurses experience high pressure at work (for accuracy in handling many patients in a short time), and errors can result in patient death (Agor, 1984). High-stake jobs like nursing are demanding, unpredictable, and require analytical decision making to make precise, but effortful decisions (Coget & Keller, 2010;Hockey, 1997). Therefore, the highly demanding work environment may require usage of an analytical processing system to produce successful outcomes (Dane & Pratt, 2007;Sinclair & Ashkanasy, 2005, p. 42).…”
Section: Extending the Jd-r Model 45mentioning
confidence: 99%